A concise introduction to mixed methods research - Creswell, John W. (2022)
"For students and researchers new to mixed methods, A Concise Introduction to Mixed Methods Research 2e by renowned author John W. Creswell provides a brief and practical introduction to mixed methods. Many graduate students and researchers in the social, behavioral and health sciences may not have the time or resources to read long treatises or stacks of journal articles on mixed methods research. This text quickly describes the basics of setting up and conducting a study using this methodology. Chapters are short and follow the process of research, from ensuring skills for conducting research, acknowledging the steps in planning a study, designing studies with increasing complexity, planning sampling strategies and integration, and writing up the results of your study. New chapters separate basic and advanced mixed methods designs for more depth, while a reorganization of chapters better align with the research process. Useful templates throughout allow readers to concretely design and organize their studies. Get started in mixed methods quickly with this brief primer"--
Includes bibliographical references and index.
Keywords: Mixed methods research; Social sciences -- Research -- Methodology; Research -- Methodology